Expression profiling during ocular development identifies 2 Nlz genes with a critical role in optic fissure closure - Brown, Jacob D. (National Academy of Sciences, 2009)
The gene networks underlying closure of the optic fissure during vertebrate eye development are poorly understood. Here, we profile global gene expression during optic fissure closure using laser capture microdissected (LCM) tissue from the margins of the fissure. From these data, we identify a unique role for the C(2)H(2) zinc finger proteins Nlz1 and Nlz2 in normal fissure closure. Gene knockdown of nlz1 and/or nlz2 in zebrafish leads to a failure of the optic fissure to close, a phenotype which closely resembles that seen in human uveal coloboma. We also identify misregulation of pax2 in the developing eye of morphant fish, suggesting that Nlz1 and Nlz2 act upstream of the Pax2 pathway in directing proper closure of the optic fissure.